Exosomes from N‐Myc amplified neuroblastoma cells induce migration and confer chemoresistance to non‐N‐Myc amplified cells: implications of intra‐tumour heterogeneity. Issue 1 (11th April 2019) - Fonseka, Pamali; Liem, Michael; Ozcitti, Cemil; Adda, Christopher G.; Ang, Ching‐Seng; Mathivanan, Suresh
ABSTRACT: Neuroblastoma accounts for 15% of childhood cancer mortality. Amplification of the oncogene N‐Myc is a well‐established poor prognostic marker for neuroblastoma. Whilst N‐Myc amplification status strongly correlates with higher tumour aggression and resistance to treatment, the role of N‐Myc in the aggressiveness of the disease is poorly understood. Exosomes are released by many cell types including cancer cells and are implicated as key mediators in cell‐cell communication via the transfer of molecular cargo. Hence, characterising the exosomal protein components from N‐Myc amplified and non‐amplified neuroblastoma cells will improve our understanding on their role in the progression of neuroblastoma. In this study, a comparative proteomic analysis of exosomes isolated from cells with varying N‐Myc amplification status was performed. Label‐free quantitative proteomic profiling revealed 968 proteins that are differentially abundant in exosomes released by the neuroblastoma cells. Gene ontology‐based analysis highlighted the enrichment of proteins involved in cell communication and signal transduction in N‐Myc amplified exosomes. Treatment of SH‐SY5Y cells with N‐Myc amplified SK‐N‐BE2 cell‐derived exosomes increased the migratory potential, colony forming abilities and conferred resistance to doxorubicin induced apoptosis. Incubation of exosomes from N‐Myc knocked down SK‐N‐BE2 cells abolished the transfer of resistance to doxorubicin induced apoptosis. These findings suggest that exosomes could play a pivotal role in N‐Myc‐driven aggressive neuroblastoma and transfer of chemoresistance between cells. Abbreviations : RNA = ribonucleic acid; DNA = deoxyribonucleic acid; FCS = foetal calf serum; NTA = nanoparticle tracking analysis; LC‐MS = liquid chromatography–mass spectrometry; KD = knockdown; LTQ = linear trap quadropole; TEM = transmission electron microscopy